Convert reimagining the prison typology through a humane reformation process - Batino, Raja; Santos, Frederick C. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
According to the World Prison Brief, the Philippines had the highest occupancy rate in the world in 2020, with a congestion rate of 538% in its jails and 310% in its prisons. The country is also grappling with an elevated recidivism rate, with estimates ranging from 70% to more than 90%.
Contemporary society perceives the modern prison as necessary institutions, which, in comparison to 18th century practices of punishment, is a more progressive and compassionate model of incarceration. However, several studies found that current systems need to be reimagined to fit the present-day requirements of the urban and social fabric.
Using spatial theories and interventions, this project seeks to address the architectural gaps in the country's correctional facilities as a key step in achieving lasting reformation, and correctional facilities as a key step in achieving lasting reformation, and subsequently reduce repeat offending and overcrowding. In the process, high rates of criminality and mortality, environmental degradation and economic loss would also be minimized.
The author believes that a comprehensive implementation of restorative justice, rehabilitation, and reintegration can be achieved by uplifting prison conditions through an architectural solution.
With cities and the environment as vital benchmarks in measuring fragility, addressing marginalized demographics such as PDLs is necessary in building a progressive and sustainable world.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Prisons -- Overcrowding; Prisons -- Philippines; Prisons -- Design and construction; Restorative justice -- Philippines